B–Sr–Nd isotopes of Miocene trachyandesites in Lhasa block of southern Tibet: Insights into petrogenesis and crustal reworking - Zhang, Miao-Yan; Hao, Lu-Lu; Wang, Qiang; Qi, Yue; Ma, Lin (Frontiers in Earth Science, 2022)
Adakitic rocks at continental collisional zones have important implications for understanding the mechanism of crustal reworking. The Himalayan-Tibetan orogen, built by India-Asia collision and Indian continental plate subduction, is one of the most prominent Cenozoic continent-continent collision zones and Cenozoic post-collisional adakitic rocks widely occurred in Lhasa block of southern Tibet. Numerous studies have suggested that the adakitic granitoids in eastern Lhasa block were derived from partial melting of a juvenile crust and post-collisional mantle-derived ultrapotassic magmas significantly contribute to this crustal reworking by energy and mass transfer. However, the genesis of adakitic rocks in western Lhasa block remains highly debated, hindering our understanding of the crustal reworking of the whole Lhasa block. Here, we report zircon U-Pb age, whole-rock major and trace elemental and Sr–Nd–B isotopic compositions for the Sailipu trachyandesites in western Lhasa block. Zircon U-Pb dating yields an eruption age of ~23 Ma. These trachyandesites are high-K calc-alkaline and exhibit intermediate SiO2 (56.9–59.6 wt.%), low MgO (2.3–4.2 wt.%) contents and low K2O/Na2O (0.8–1.1) ratios, and enrichment in light rare earth elements (LREEs), depletion in heavy REEs (HREEs) with negligible Eu and Sr anomalies. They have high Sr (1080–1593 ppm), and low Y (14.0–26.8 ppm) and Yb (1.08–1.48 ppm) contents, with relatively high Sr/Y (46–95) and La/Yb (46–77) ratios, showing close adakitic affinities. These Sailipu adakitic rocks display δ11B values of -9.7 to -2.7‰, which are higher than those of MORBs but similar to those of arc lavas, indicating contributions of the juvenile crust. However, they show much more enriched Sr–Nd isotopes (87Sr/86Sr(i)=0.7092–0.7095, εNd(t) = -8.09 to -7.25) than the juvenile crust, indicating contributions of ultrapotassic magmas. Thus, the Sailipu adakitic rocks are likely generated by the interaction between juvenile lower crust and underplated ultrapotassic magmas. Combined with adakitic magmatism in eastern Lhasa block, we suggested that magma underplating and subsequent crust-mantle mixing could have been a common and important process that induces the reworking of the juvenile crust beneath southern Tibet. This process may be related to the foundering of subducted Indian continental slab.